Perspectives on high-intensity interval exercise for health promotion in children and adolescents - Bond, Bert (Open Access J Sports Med, 2017)
Physical activity lowers future cardiovascular disease (CVD) risk; however, few children and adolescents achieve the recommended minimum amount of daily activity. Accordingly, there is virtue in identifying the efficacy of small volumes of high-intensity exercise for health benefits in children and adolescents for the primary prevention of CVD risk. The purpose of this narrative review is to provide a novel overview of the available literature concerning high-intensity interval-exercise (HIIE) interventions in children and adolescents. Specifically, the following areas are addressed: 1) outlining the health benefits observed following a single bout of HIIE, 2) reviewing the role of HIIE training in the management of pediatric obesity, and 3) discussing the effectiveness of school-based HIIE training. In total, 39 HIIE intervention studies were included in this review. Based upon the available data, a single bout of high-intensity exercise provides a potent stimulus for favorable, acute changes across a range of cardiometabolic outcomes that are often superior to a comparative bout of moderate-intensity exercise (14 studies reviewed). HIIE also promotes improvements in cardiorespiratory fitness and cardiometabolic health status in overweight and obese children and adolescents (10 studies reviewed) and when delivered in the school setting (15 studies reviewed). We thus conclude that high-intensity exercise is a feasible and potent method of improving a range of cardiometabolic outcomes in children and adolescents. However, further work is needed to optimize the delivery of HIIE interventions in terms of participant enjoyment and acceptability, to include a wider range of health outcomes, and to control for important confounding variables (eg, changes in diet and habitual physical activity). Finally, research into the application of HIIE training interventions to children and adolescents of different ages, sexes, pubertal status, and sociocultural backgrounds is required.